PERAN ASEAN DAN MASYARAKAT SIPIL TRANSNASIONAL DALAM TRANSISI DEMOKRASI DI BURMA PASCA-PEMILU - Haripin, Muhamad; Arumsari, Mutiara (UI Scholars Hub, 2010)
The recent Burma election has drawn international criticism for its aim to legitimize the prolonged reign of military's role in militarized civilian role. While there have been different responses from ASEAN and neighbouring countries, transnational civil society in the region reacted along similar tone of condemnation. The ultimate goal of this essay is to analize how both sides played their role on the issue of Burma’s transition and how they reacted to the election itself. The result indicates that ASEAN arid neighboring countries remain incoherent and rather faible on their political support to democracy in Burma, given conflict of interests withm the organization. On the other hand, albeit its strong advocacy, the efforts of transnational civil society in ASEAN to advance the issue faced difficulties in several ways. Drawing on obstacles on both sides, one way forward is to seize such post-election momentum through promoting the National Reconciliation agenda in a cooperative manner.